Submucosal Myoma Treatment for Women Who Wish to have Children in the Future Nodule Dissection Centripetal Cutting Method of TCR (Transcervical Resection) - Inoue, Shigeo (The Surgery Journal, 2020)
Due to the recent trend to marry later, patients with uterine myoma, and who wish to preserve their uterus have increased, are leading to greater demand for minimally invasive myomectomies. For intramural myomas and submucosal myomas, which are located near the uterine cavity, which are high risk for sterility or infertility, incision of the myometrium, and suture to the uterine cavity during laparoscopic myomectomy is required, and Caesarean section is frequently selected as the child delivery method. Hysteroscopic myomectomy is advantageous for persons wishing for pregnancy. The abdominal wall is not damaged, and there is less pain and a shorter hospital stay. Hysteroscopic myomectomy does not cause postoperative intraperitoneal adhesion, contraceptive period is shorter, and vaginal delivery is also possible. Since expensive disposal surgical instrument, surgery assistants are not needed, it also contributes to medical economy, and its widespread is desired. On the other hand, learning the technique is difficult, since unique complications may occur and only an endoscope in the specific field of vision, the uterine cavity is used for this procedure. If only cases with small submucosal myoma are indicated for hysteroscopic myomectomy, technical improvement and wider adoption will not occur. However, if the indication can be correctly recognized and a safe and accurate technique be acquired, adoption of hysteroscopic myomectomy could actually be widened. It is an excellent technique which can become mainstream for fibroid treatment.
Keywords: transcervical resection; hysteroscopic myomectomy; sterility; infertility